International Mobility Based on Women Labour: Study of Changes in Socio-Economic-Cultural Family Former migrant worker Jakatawa Bulaksari In the village, District Bantarsari, Cilacap Seen From the Perspective of Islamic Economic Theory - Abdul Haris; Siti Nur Azizah (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2018)
Migration is marked by international mobility occurs due to population growth which is not matched by the growth of employment. For women in the village who do not have a higher education and do not have a lot of skills, international mobility is a golden opportunity to improve their families' income. This issue is very complex but interesting to be studied. One of the purpose of this study was to Assess the social, economic, and cultural communities Jakatawa Bulaksari in general, particularly family / former international migrant workers (TKW) before becoming migrant workers, as well as how Islam views women migrant workers, it is well known that in Islam there are three pillars used to build the economic system in the Islamic view, that is how the wealth acquired over ownership (al-milkiyah), and how the management of property ownership (tasharruf fil milkiyah), as well as how the distribution of wealth in society (tauzi'ul tsarwah bayna an- Hoodoo). These three pillars, according to the researchers, the relevant applied in the case of Indonesian Workers (TKI), especially Labor Women (TKW) which is the object of this study were associated with changes in the behavior of economic, social, and cultural. This research was conducted by survey method is the explanation of descriptive research. This research was conducted in the area of Dusun Jakatawa, Bulaksari Village, District Bantarsari, Cilacap. Based on the findings availability of jobs in the hamlet jakatawa was very limited, coupled with limited human resources in the management of agricultural land, as well as the most supportive factor is the lifestyle of a consumer society, lack of education, which raises Hamlet jakatawa option for women to work outside the country.